Написи на івриті на керамічній посудині XVII—XVIII ст. - Прищепа, Б.А.; Русакова, Ю.М.; Чміль, Л.В. (Археологія, 2023)
Статтю присвячено аналізу єврейських написів на
керамічному посуді XVII—XVIII ст. із Києва, Білої
Церкви й Острога. Такі епіграфічні пам’ятки вперше вводяться до наукового обігу в Україні. In the article the authors deal with the verification, attribution and introduction into scientific circulation of a number of Hebrew
inscriptions on Early Modern ceramic vessels. This issue has not been raised in the Ukrainian archaeological publications yet.
Such isolated inscriptions were previously wrongly interpreted as potters’ marks. More than a dozen of vessels with inscriptions
in Hebrew are known today. In particular, they were found during the excavations of three cities — Bila Tserkva, Kyiv, Ostroh.
These are fragments of three plates, two small and one large mugs, which come from the cellar of the first half of the 17th century
in Ostroh, two plates and a mug from the building of the late 17th — early 18th centuries in Bila Tserkva, as well as a pot from
the building of the 17th century in Kyiv.
Two groups of inscriptions can be distinguished. The first one is Passover inscriptions on vessels that were obviously intended
for the Passover Seder (a symbolic set of products for a holiday supper) or for daily usage during the holiday. Using an additional
set of vessels to the holiday is explained by kashrut norms and specific prohibitions of kvass use. The mug with an inscription
“kimkha de Piskha” (“flour for Pesach”) belongs to the second group. It was associated exclusively with religious needs and was
intended for the collection of donations (tzadaka) on Passover. Tzadaka as a religious obligation to perform charity laid at the
basis of the Jewish community existence. It led to the proliferation of different types of money boxes for collecting donations.
In general, the topic requires detailed investigations with the involvement of additional archaeological materials, interpretation
and introduction of hitherto unpublished materials into scientific circulation.